Pharmacopuncture in Korea: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (6th January 2016) - Park, Jimin; Lee, Hyangsook; Shin, Byung-Cheul; Lee, Myeong Soo; Kim, Boryang; Kim, Jong-In
Abstract : Background . Pharmacopuncture is a new form of acupuncture combining acupuncture with herbal medicine, and it has been used under various conditions in Korea. The aim of this study is to establish clinical evidence for the safety and efficacy of pharmacopuncture in Korea. Methods . We searched 9 databases and two relevant journals up to December 2014 using keywords, such as pharmacopuncture. All randomized, controlled trials evaluating pharmacopuncture under any conditions in Korea were considered. Results . Twenty-nine studies involving 1, 211 participants were included. A meta-analysis of two studies on obesity showed that 5 to 8 weeks of pharmacopuncture reduced weight, waist circumference, and body mass index (BMI) more than normal saline injections. In the 5 studies of musculoskeletal conditions, 7 to 30 days of pharmacopuncture had additional effects on the reduction of pain intensity, and this benefit was maintained by limiting analyses to studies with a low risk of bias for randomization and/or allocation concealment. Conclusions . This systematic review suggests the potential of pharmacopuncture for obesity and musculoskeletal diseases. However, it is difficult to recommend pharmacopuncture as an evidence-based treatment because of methodological flaws and small sample sizes of the included studies. Further well-designed trials are needed to draw a definitive conclusion.